Posterior Corneal Surface Stability after Femtosecond Laser-Assisted Keratomileusis - Carlo Cagini; Marco Messina; Marco Lupidi; Francesco Piccinelli; Tito Fiore; Daniela Fruttini; Leopoldo Spadea (Journal of Ophthalmology, 2015)
The purpose of this study was to evaluate posterior corneal surface variation after femtosecond laser-assisted keratomileusis in patients with myopia and myopic astigmatism. Patients were evaluated by corneal tomography preoperatively and at 1, 6, and 12 months. We analyzed changes in the posterior corneal curvature, posterior corneal elevation, and anterior chamber depth. Moreover, we explored correlation between corneal ablation depth, residual corneal thickness, percentage of ablated corneal tissue, and preoperative corneal thickness. During follow-up, the posterior corneal surface did not have a significant forward corneal shift: no significant linear relationships emerged between the anterior displacement of the posterior corneal surface and corneal ablation depth, residual corneal thickness, or percentage of ablated corneal tissue.